2003
DOI: 10.1094/cm-2003-1029-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Use of Soil Electroconductivity in a Multistage Soil-Sampling Scheme

Abstract: The inherent variability of pasturelands makes it difficult to sample soils and accurately characterize a pasture. Indirect methods such as soil electroconductivity (EC) can be used to rapidly, noninvasively, and inexpensively quantify soil variability. The objective of this study was to determine if rapidly collected, georeferenced soil information could be used to propose an accurate, multistage sampling scheme for five soil variables in a central Iowa pasture. Results from this study suggest that the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Sampling points were arranged in a triangular grid with inter‐ and intrarow separation distances of 6 m. To obtain data from samples located closer than 6 m, an additional point was sampled within each row at randomly chosen 1‐ or 2‐m separation distances. An earlier study of the pasture site indicated short‐range variation in soil characteristics such as soil P, K, pH, and organic matter (Tarr et al, 2003). As a result, this short‐range variation in soil samples was investigated to obtain a more reliable experimental semivariogram model (Burgess and Webster, 1980; Kravchenko and Bullock, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Sampling points were arranged in a triangular grid with inter‐ and intrarow separation distances of 6 m. To obtain data from samples located closer than 6 m, an additional point was sampled within each row at randomly chosen 1‐ or 2‐m separation distances. An earlier study of the pasture site indicated short‐range variation in soil characteristics such as soil P, K, pH, and organic matter (Tarr et al, 2003). As a result, this short‐range variation in soil samples was investigated to obtain a more reliable experimental semivariogram model (Burgess and Webster, 1980; Kravchenko and Bullock, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Horney et al [ 92 ] suggested a methodology for salt affected soils with the following steps: (1) building an EC a map; (2) directed sampling for salinity; (3) as a function in the field determination of the estimated improvement requirement and (4) integration into a practical spatial pattern. Tarr et al [ 245 ] used stratification of EC a and terrain attributes to derive a heterogeneous pasture in relatively homogenous sampling zones with fuzzy k-means clustering. The five zones had significant differences in the target variables (i.e., P, K, pH, organic matter and water content).…”
Section: Detecting Soil-related Properties In Non-saline Soils By mentioning
confidence: 99%
“…The advantage of benchmark sampling is that by consistently sampling from the same benchmark sites over time, changes in soil nutrient trends can be monitored [4]. Due to soil variability, different sampling designs attempt to find representative points of a field with the help of different sensory information (e.g., electrical conductivity of the soil) [14,15]. Another sampling scheme acts in multiple stages, where first, a large number of points are generated and then filtered based on some criteria [16].…”
Section: Benchmark Soil Samplingmentioning
confidence: 99%